A restudy of Early Devonian graptolites from the Himalayan Mountains, southern Xizang, China. (26th August 2021) - Chen, Qing; Chen, Xu; Zhang, Linna; Muir, Lucy A.
Abstract : Early Devonian graptolites from the Liangquan Formation at a locality north of Jiacun, Nielamu, southern Xizang, were collected more than 50 years ago and are restudied herein. Based on morphological analysis of tubarium features, the eight species belonging to two genera identified in previous studies were revised and merged into four species: Neomonograptus himalayensis, Uncinatograptus nyalamensis, Uncinatograptus thomasi, and Uncinatograptus yukonensis . The co‐occurrence of U. thomasi and U. yukonensis indicates a late Pragian to early Emsian age ( U . yukonensis Biozone). Abstract : Early Devonian graptolites from the Liangquan Formation at a locality north of Jiacun, Nielamu, southern Xizang, are restudied. On the basis of morphological analysis of tubarium features, the eight species belonging to two genera identified in previous studies were revised and merged into four species: Neomonograptus himalayensis, Uncinatograptus nyalamensis, Uncinatograptus thomasi, and Uncinatograptus yukonensis . The co‐occurrence of U. thomasi and U. yukonensis indicates a late Pragian to early Emsian age ( U . yukonensis Biozone).